Ensayo para el enraizamiento de acodos aereos de Magnolia grandiflora L. (Magnoliaceae) - hernandez Gil, R.=700 1 Almeida P, J.A.
(Es, En)
Ilus., 5 ref.
Keywords: MAGNOLIA GRANDIFLORA; ENRAIZAMIENTO; ACODO; ACIDO INDOLBUTILICO; VENEZUELA; PITTIERIA